Hak Pakai Atas Tanah Hak Milik dan Penyelesaian Sengketa - Suryani Sappe; Adonia Ivone Latturete; Novyta Uktolseja (Faculty of Law, Universitas Pattimura, 2021)
The process of the occurrence of use rights over land is based on statutory regulations and government regulations to prevent misuse of the administration process. However, in this era of increasingly modern life, there are many disputes relating to control and use of land for public, individual and private interests. The right to use is not at all a new land rights institution, but it is less well known than the ownership rights, land use rights, or building use rights, for that it requires a correct understanding of the right to use in order to use it responsibly. The purpose of this paper is to study and analyze the arrangements for use rights over land with ownership rights and to study and analyze the process of settling usufructuary disputes over land with ownership rights. The method used in this research is the normative juridical method using the statute approach and the conceptual approach, and the case approach is then studied and used as material for descriptive analysis in order to obtain answers to the problems that occur. The results of the research show that the regulation of use rights over land with ownership rights is very important because, when the right to use stands, buildings or objects become assets of the recipient of the right to use. So when the right of use expires or is canceled it will have a legal effect on the objects on it, thus it is hoped that there must be regulations governing objects or buildings that are included in the relinquishment of use rights even though there is an agreement made by the parties.